2008
DOI: 10.1681/asn.2007050581
|View full text |Cite
|
Sign up to set email alerts
|

The Death Ligand TRAIL in Diabetic Nephropathy

Abstract: Apoptotic cell death contributes to diabetic nephropathy (DN), but its role is not well understood. The tubulointerstitium from DN biopsy specimens was microdissected, and expression profiles of genes related to apoptosis were analyzed. A total of 112 (25%) of 455 cell death-related genes were found to be significantly differentially regulated. Among those that showed the greatest changes in regulation were two death receptors, OPG (the gene encoding osteoprotegerin) and Fas, and the death ligand TRAIL. Glomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(143 citation statements)
references
References 48 publications
3
140
0
Order By: Relevance
“…A recent study has observed that osteoprotegerin is strongly upregulated at the RNA level in kidney samples from patients with diabetes [37]. This is interesting in relation to our observation that osteoprotegerin concentration predicts ESRD.…”
Section: Discussionsupporting
confidence: 81%
“…A recent study has observed that osteoprotegerin is strongly upregulated at the RNA level in kidney samples from patients with diabetes [37]. This is interesting in relation to our observation that osteoprotegerin concentration predicts ESRD.…”
Section: Discussionsupporting
confidence: 81%
“…Histology and immunohistochemistry. Following the previously described protocol (19), immunohistochemistry studies were performed from an independent cohort of control subjects (histologically verified unaffected regions from tumor nephrectomies), type 2 progressive diabetic nephropathy case subjects, and other kidney disease biopsies (online appendix Table 3). Jak2 staining was performed using a primary monoclonal antibody at 1:100 (AHO1352; Biosource, Camarillo, CA).…”
Section: Methodsmentioning
confidence: 99%
“…51 TNF or TNF-related apoptosis-induced ligand activates simultaneous death and NF-B-dependent survival signals in renal cells. 52 Inhibition of NF-B in these circumstances promotes cell death; however, NF-B/RelA activation is involved in the apoptosis of podocytes in HIV-transgenic mice mediated by NF-B-dependent Fas and Fas ligand expression in nephrotoxin and ischemia-induced tubular cell apoptosis. 42,49,53,54 …”
Section: Regulation Of Transcriptionmentioning
confidence: 99%